Uterine defense modulation for the treatment of repeat breeding due to infectious endometritis in bovines - Saini, P S; Nanda, A S; Grewal, A S; Singh, Jagir (The Indian Journal of Animal Sciences, 2012)
The selected cows (n=54) were randomly assigned to one of the 4 treatment groups to study the effect of immunomodulators on uterine defense mechanism (UDM) in repeat breeding bovines. The treatment was started during estrus (day 0). Cows in group A (n =10) were given autologous plasma (50 ml IU daily for 3 days) in group B (n=8) levamisole (2.5 mg/sc) on days 0, 2, 6, 10, 14 and 18 of the estrous cycle, in group C (n=8) autologous plasma and levamisole, in group D (n=18) E.coli lipopolysaccharide (LPS, 100 Âµg IU single dose), and group E (n=10) gentamicin (400 mg IU daily for 4 days). The animals were inseminated during estrus following treatment. In groups D, E, B, C and A, 14 (78%), 8 (80%), 4 (50%), 3 (37%) and 2 (20%) cows, respectively, conceived within 3 successive insemminations. It was concluded that intrauterine E. coli LPS infusion effectively improved stimulation of non-specific (cellular) immunity and elimination of endometritis.